2000
DOI: 10.1002/chin.200032050
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Surface‐Mediated Reactions. Part 8. Oxidation of Sulfides and Sulfoxides with tert‐Butyl Hydroperoxide and OXONE.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Heterogeneous catalysts promote oxidation reactions via attracting oxygen from oxidants, such as TBHP (tert-BuO 2 H) and HP (H 2 O 2 ) [39,40]. In the last decade, TBHP has been used as oxidant for various oxidation reactions such as alkyl benzene and benzyl alcohol oxidation.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Heterogeneous catalysts promote oxidation reactions via attracting oxygen from oxidants, such as TBHP (tert-BuO 2 H) and HP (H 2 O 2 ) [39,40]. In the last decade, TBHP has been used as oxidant for various oxidation reactions such as alkyl benzene and benzyl alcohol oxidation.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…These studies afforded insights into the mechanism of surface-mediated processes. It was found that oxidation of sulfides or sulfoxides by TBHP/silica gel occurs at least predominantly via nucleophilic attack by the substrate molecule on the hydroperoxide, which is activated by being bound to isolated silanol sites on the silica gel surface [271].…”
Section: Other Catalystsmentioning
confidence: 99%
“…All forms of silica contain the Si−O bone, 44 a kind of stable Lewis acid site. Taking the advantages of the rich porous structure, high chemical stability, abundant surface hydroxyl groups, and low cost, silica gels have been widely used as adsorbents, 45,46 supporting materials, 47,48 and catalysts 49,50 in various applications, such as adsorptive removal of water contaminants, chromatographic analyses, etc. Zhang and Wang 51 reported a core−shell microsphere catalyst incorporated with a solid silica core and mesoporous shell for dibenzothiophene oxidation, which yielded a 98% of DBT conversion rate from simulated oil.…”
Section: Introductionmentioning
confidence: 99%
“…With the presence of isolated and associated silanol sites on the silica surface, silica can be used to mediate the oxidation of sulfides and sulfoxides with (CH 3 ) 3 COOH and OXONE, and result in reasonably high selectivity to sulfoxides. 49 Stanger and Angelici 50 reported the silica-catalyzed oxidation of DBT and 4,6-DMDBT by TBHP. It appears that the silica materials have the prospect of oxidative desulfurization, but the more accurate mechanism of oxidative desulfurization needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%